2017
DOI: 10.1111/crj.12734
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of different methods for obtaining transbronchial lung cryobiopsy in diffuse lung diseases

Abstract: Transbronchial lung cryobiopsy was found to offer a reasonable yield in the diagnosis of DPLDs. The incidence of pneumothorax and moderate-to-severe bleeding was lower with the use of fluoroscopy and an occlusion balloon, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 36 publications
0
65
0
1
Order By: Relevance
“…The expert statement published subsequent to the completion of this study recommends 3-5 biopsies per patient, though the authors acknowledge that "the optimal number of biopsies cannot be uniformly established" [10]. While increased diagnostic yield has been reported in studies where sampling was performed from more than one bronchial segment [12], complication rates were also higher [12,13]. Future studies are required to determine if CT-fluoroscopy allows increased biopsy number without a concomitant increased complication rate.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The expert statement published subsequent to the completion of this study recommends 3-5 biopsies per patient, though the authors acknowledge that "the optimal number of biopsies cannot be uniformly established" [10]. While increased diagnostic yield has been reported in studies where sampling was performed from more than one bronchial segment [12], complication rates were also higher [12,13]. Future studies are required to determine if CT-fluoroscopy allows increased biopsy number without a concomitant increased complication rate.…”
Section: Discussionmentioning
confidence: 98%
“…High rates of complications have been observed in procedures per- formed without fluoroscopic vision [13,19], and subsequent comment has noted the importance of fluoroscopic guidance during transbronchial cryobiopsy [20]. It is possible that high complication rates observed in some studies utilizing fluoroscopy are a result of sub-optimal imaging achieved by 2-D C-arm fluoroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dhooria et al [23] reported the outcomes of TBLC carried out in different ways – with and without the fluoroscopic guidance and with and without the bronchial blocker. The study showed that fewer pneumothoraces and moderate-to-severe bleeding were observed using fluoroscopy and bronchial blocker, respectively [23].…”
Section: Different Approachesmentioning
confidence: 99%
“…The study showed that fewer pneumothoraces and moderate-to-severe bleeding were observed using fluoroscopy and bronchial blocker, respectively [23]. Alternatively, two scopes alternated during the procedure may avoid the need for intubation [24].…”
Section: Different Approachesmentioning
confidence: 99%